REDESAIN BRAKE COOLING DUCT PADA REM CAKRAM DEPAN SEPEDA MOTOR; ANALISIS PERUBAHAN TEMPERATUR DENGAN METODE COMPUTATIONAL FLUID DYNAMICS (CFD) - Sofana , Ilyas; Choirul Anam, Mochammad; Musthofa, Imron (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2024)
Brake Cooling Duct is a useful technology to drain air from the front so that the brake caliper & brake disc do not overheat. Another benefit is to keep the engine temperature normal because the it always gets fresh air. This study adds an air duct design or brake cooling duct to cool the brake disc using ANSYS CFD simulation with speeds of 48 Km/h and 98 Km/h to get the temperature of the brake disc when braking without cooling duct and using brake cooling duct, the difference in heat flux value after adding air duct/brake cooling duct, the process of temperature changes that occur when the air flow from the brake cooling duct touches the surface of the brake disc with speeds of 48 Km/h and 96 Km/h. The results obtained brake disc temperature when braking without cooling duct with a maximum temperature value of 137.74 ºC and using brake cooling duct with air inlet speed of 48 Km/h is a maximum of 74.73ºc and 98 Km/h is 73.42 ºc. There is a difference in heat flux value after adding an air duct / brake cooling duct of 33116 W/m2 with a speed of 48 Km/h and 33746 W/m2 with a speed of 96 Km/h. The temperature change that occurs when the air flow from the brake cooling duct touches the surface of the brake disc with a speed of 48 Km/h is 58.97º C, for a speed of 96 Km/h is 60.26º C. Keywords : Brake cooling duct , CFD, heat transfer, simulatioan temperature disk brake